Effectiveness of Health Education on Children's Knowledge About Sexual Violence in School-Age Children - Irman, Veolina; Saridewi, Ratna Indah (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: The current spike in cases of sexual violence against children continues to rise; therefore, more health education is needed in the community. Health education supports health programs that produce changes and increase knowledge in a short time. This research aims to determine the effectiveness of health education on children's level of knowledge about sexual violence in school-aged children at SDN 02 Tarandam, Padang City in 2024. Methods: This type of research was quantitative research with a quasi-experimental research design using a one-group pre-test post-test design. The population of this study was class V students, totaling 23 people. The research was conducted at SDN 02 Tarandam, Padang City. Sampling was carried out using a total sampling technique. Data was collected through questionnaires and analyzed using the T-test. Results: The research results showed that the average level of knowledge of children about sexual violence before receiving health education was 5.96, and after receiving health education, it was 8.09, with a p-value of <0.001. Conclusion: The research concluded that there was an influence of health education on children's level of knowledge about sexual violence in school-aged children. It is hoped that the school will submit a request to the relevant Health Service to provide health education about sexual violence to increase children's knowledge about sexual violence in school-aged children.